Securing the Digital Landscape: Present Concerns and Hurdles in Digital Rights Management - S, Ravichandra H (Journal of Global Economy, Business and Finance, 2024)
The landscape of Digital Rights Management (DRM) is witnessing continual evolution, marked by emerging issues and challenges that demand attention and adaptation. As technology advances, DRM faces the complex task of balancing copyright protection with user rights and expectations. One prominent challenge lies in the realm of interoperability, where varying DRM systems can create barriers for users seeking seamless access to content across different platforms. Privacy concerns have also come to the forefront, as DRM systems often involve the collection of user data to enforce licensing and access controls. Striking the right balance between effective content protections and safeguarding user privacy poses a delicate challenge for DRM implementation. Furthermore, the rise of streaming services and the proliferation of diverse digital platforms increasethe demand for standardized DRM solutions. In the absence of universally accepted standards, fragmentation and compatibility issues can arise, affecting both content providers and consumers. As the digital environment undergoes globalization, the significance of legal and regulatory frameworks will grow, playing a crucial role in influencing the future of DRM. Navigating the complexities of international law and dealing with jurisdictional differences are additional barriers to the effective deployment of DRM. Essentially, the emerging issues and challenges in Digital Rights Management highlight the importance of a dynamic and collaborative approach to ensuring intellectual property protection while respecting the constantly changing demands and rights of digital content consumers.